Kontribusi Kearifan Lokal Yogyakarta: Metode Memilih Kayu bagi Desain Produk untuk Interior - Setya Budi Astanto (Institut Seni Indonesia Yogyakarta, 2016)
A local wisdom ofYogyakarta contains a method on how to choose the good woodjust by looking at a glance the silhouette of the wood. This method is easy and can be implemented by everyperson without a special supporting tool.It's better for an interior designerto understand local widom in his closest environment to offer an optimal to the surrounding environment. Meanwhile, global environment problems are everybody's responsibility so that it will be better if everybody can make a contribution in offering a design solution to the surrounding environmental problem.The qualitative method in this research collected all the significant data from informants comprising both narrative and visual ones. This research is relevant to the present urban community's environmental requirements, especially about how toprevent threat to trees in rural area. By this research a lot of people is expected to understand why nailing trees or scratching them areforbidden because trees that have been hurted will produce bad timbers. Based on this conditions interior designers should have smart solutions using nature as their inspirations; this is commonly called biomimicry design.Keywords: sustainble interior design, biomimicry, local wisdom of Yogyakarta, method of choosing log timber.